Eksistensi Khiyar Dalam Perkembangan Transaksi Jual Beli - Muhamad Izazi Nurjaman; Januri Januri; Neni Nuraeni (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This study describes a discussion about the existence of khiyar's position in the development of buying and selling transactions. By using a descriptive method that is literature in nature, this study found the fact that the position of the existence of the khiyar concept was inseparable from the position of the existence of buying and selling transactions that had developed as the main contract. Its position is relative. That is, it is still enforced by some economic actors and is also eliminated because it creates uncertainty. As for what needs to be considered is the concept of khiyar as a complementary requirement. So that without the concept of khiyar in a transaction it will not damage the validity of the transaction. However, its existence is the best way to make the contract more legitimate and ideal along with achieving a level of benefit for the parties who carry it out.